Model E-Commerce Keripik Pisang - Herliawan Dimas Aji (Balitbangda Provinsi Lampung, 2015)
Web Technology has important roles and allow organizations and companies to enter the market easily, inexpensively, and without geographical restrictions. The aim of this study was to design banana chips e-commerce model. This study was carried out by a structured method with SDLC models (System Development Life Cycle). The results showed that banana chips ecommerce model obtained several advantages which include customer service and be a good corporate image. Model of e-commerce that have been made have features that can simplify the process of buying and selling customers.